2021
DOI: 10.3991/ijim.v15i05.18703
|View full text |Cite
|
Sign up to set email alerts
|

Digital Mind Map Assisted Group Investigation Learning for College Students’ Creativity

Abstract: This study aimed to investigate the effect of a digital mind map (DMM) assisted group investigation (GI) on students’ creativity in higher education. A pre-test post-test nonequivalent control group design was employed in this study. The study was conducted in 2019/2020 to 75 fifth semester students from IKIP Budi Utomo Malang, Indonesia. The data were collected using a pre-test and a post-test on students’ creativity. The students’ creative performance was evaluated using a rubric assessing the keywords, mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Mind maps, in addition to being a learning tool, can also be used as an evaluation tool. According to Evrialiani Rosba et al, a Digital Mind Map (DMM) can be used to evaluate students' creativity products [20].…”
Section: Discussionmentioning
confidence: 99%
“…Mind maps, in addition to being a learning tool, can also be used as an evaluation tool. According to Evrialiani Rosba et al, a Digital Mind Map (DMM) can be used to evaluate students' creativity products [20].…”
Section: Discussionmentioning
confidence: 99%
“…Scholars (e.g., Liu et al, 2014 ; Hazaymeh and Alomery, 2022 ) suggested that applying mind mapping using software or an application led to more learning gains. It is likely because digital technologies make mind mapping an interactive fun-filled activity that enhances students’ motivation and satisfaction ( Rosba et al, 2021 ). Another advantage of digital mind mapping is that it facilitates collaborative work in small groups ( Wang, 2019 ) so that the idea exchange and brainstorming among group members can further stimulate students’ creativity.…”
Section: Discussionmentioning
confidence: 99%
“…Mind mapping is very useful in improving the function of the brain's work, if the student has become accustomed to making a mind map then automatically he will be faster in processing or understanding the material being studied. The use of simple keywords in mind mapping will also help in remembering important materials related to the main idea (Rosba et al, 2021).…”
Section: Improve a Person's Ability To Understand Somethingmentioning
confidence: 99%
“…A person influences and is influenced by the environment in which he is located, thus changes in the individual as well as in the environment can support or can hinder creative efforts (Hidayati et al, 2019;Rosba et al, 2021).…”
Section: Introductionmentioning
confidence: 99%